Validation of the generalized anxiety disorder scales (GAD-7 and GAD-2) in primary care settings in Latvia - Vrublevska, Jelena; Renemane, Lubova; Kivite-Urtane, Anda; Rancans, Elmars (Frontiers in Psychiatry, 2022)
Background: Anxiety disorders are the most prevalent mental disorders in the world and have an important impact on the global burden of disease. Generalized anxiety disorder (GAD) is the most prevalent anxiety disorder encountered in primary care. There are no available validated anxiety screening tools in primary care in Latvia. We aimed to validate both a seven-item and a two-item Generalized Anxiety Disorder scale (GAD-7 and GAD-2) in the Latvian and Russian languages, to detect generalized anxiety disorder (GAD) in primary care settings in Latvia. Methods: During a 1-week period, all patients aged 18 years or older visiting their GP (general practitioners) with any health concern at 24 primary care settings throughout Latvia were invited to complete the GAD-7 in their native language (Latvian or Russian). Criterion validity was assessed against the Mini International Neuropsychiatric Interview (MINI). Results: The study sample included 1,459 participants who completed the GAD-7 and the MINI. The GAD-7 items showed good internal reliability (Cronbach’s alpha 0.87 for Latvian version and 0.85 for Russian version (for Latvia) of the GAD-7). A cut-off score for detecting GAD of 5 or above was estimated for Latvian version of the GAD-7 (sensitivity 75.4%, specificity 68.9%, respectively) and 7 or above for Russian version of the GAD-7 (sensitivity 73.3%, specificity 84.1%, respectively). The internal reliability of the GAD-2 was lower for both languages (Cronbach’s alpha 0.75 for Latvian version and 0.68 for Russian version of the GAD-2). A cut-off score of 2 or above was established for both the Latvian, and Russian versions of the GAD-2 (sensitivity 78.9% and 83.3%; specificity 63.7% and 69.1% for the Latvian and Russian versions of the GAD-2, accordingly) for detecting GAD. Conclusions: This is the first study to report criterion validity of the Latvian and Russian (for Latvia) versions of the GAD-7 and GAD-2, assessed in a nationwide study conducted at the primary care level.